Challenges in antenatal care utilization in Kandahar, Afghanistan: A cross-sectional analytical study - Bilal Ahmad Rahimi; Enayatullah Mohamadi; Muhibullah Maku; Mohammad Dawood Hemat; Khushhal Farooqi; Bashir Ahmad Mahboobi; Ghulam Mohayuddin Mudaser; Walter R. Taylor (PLoS ONE, 2022)
Background Quality antenatal care (ANC) is one of the four pillars of safe motherhood initiatives and improves the survival and health of mother and neonate. The main objective of this study was to assess the barriers in the utilization of ANC services in Kandahar, Afghanistan. Methods This was a cross-sectional analytical study conducted over one year from December 2018–November 2019. Data were analyzed by descriptive statistics, Chi squared, and binary logistic regression. Results A total of 1524 women were recruited in this study with mean age of 30.3 years. Of these women, 848 (55.6%) were rural dwellers, 1450/1510 (96.0%) were illiterate, 438/608 (72.0%) belonged to low-income families, 1112/1508 (73.7%) lived in joint families, 1420/1484 (95.7%) lived in a house of >10 inhabitants, while 388/1494 (26.0%) had attended had at least one ANC visit during their last pregnancy. On univariate analysis, the main barriers in the utilization of ANC services were living in rural areas, being illiterate, having lower socio-economic status, remoteness of the health facility from home, bad behavior of clinic personnel, and unplanned pregnancy. Only lower socio-economic status and bad behavior of clinic personnel were independent explanatory variables in the regression model. Conclusions Utilization of ANC services is inadequate in Kandahar province. Improving clinic staff professional behavior and status of women by expanding educational opportunities, and enhancing community awareness of the value of ANC are recommended.